1993
DOI: 10.1029/92wr02420
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for improvements in drinking water quality

Abstract: In this paper, data from a 1991 survey of Georgia residents were used to study people's willingness to pay (WTP) for improvements in drinking water quality and people's perceptions of potential groundwater contamination. Results showed that 27% of the respondents served by public water supplies rated drinking water quality as poor, and 23% were uncertain about their drinking water quality. The contingent valuation method was used to estimate WTP using a checklist format. The median estimated WTP was $5.49 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…Alberini et al (1997) found educational attainment to be a statistically significant determinant of the WTP. Jordan and Elnagheeb (1993) have also found the education variable to be positive and significant indicating that respondents with a higher level of education were willing to pay more than respondents with a lower level of education. Awareness really matters in a CV study where a hypothetical scenario is presented to the respondents.…”
Section: Explanatory Variables Of Willingness To Paymentioning
confidence: 88%
See 2 more Smart Citations
“…Alberini et al (1997) found educational attainment to be a statistically significant determinant of the WTP. Jordan and Elnagheeb (1993) have also found the education variable to be positive and significant indicating that respondents with a higher level of education were willing to pay more than respondents with a lower level of education. Awareness really matters in a CV study where a hypothetical scenario is presented to the respondents.…”
Section: Explanatory Variables Of Willingness To Paymentioning
confidence: 88%
“…The mean or median WTP for the households which already have a municipal surface water supply connection is less than those not having a surface water supply connection. Jordan and Elnagheeb (1993) in their study found that private well water users were willing to pay more than households using the public water supply system. They concluded that as people connected to the public water supply system are presently paying the water companies for water, they are less willing to pay.…”
Section: Explanatory Variables Of Willingness To Paymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies can be categorized by how the valuation "scenarios" are structured. One group follows Edwards' lead by specifying an "objective hypothetical" initial exposure condition and an alternative hypothetical improvement [Jordan and Elnagheeb, 1993;Sparco, 1995;Crutchfield et al, 1997;Delavan, 1996]. Other studies have allowed respondents to specify their own "subjective" probabilities of exceeding health standards [Sun et al, 1992;Poe, 1993] or perceptions of current safety levels [Powell, 1991], with the target being the reduction of the probability of exceeding standards to zero or the improvement of water quality to safe levels.…”
Section: Introductionmentioning
confidence: 99%
“…In their reserach on willingness to pay for improvements in the quality of drinking water Jordan and Elnagheeb (1993) in Georgia, United States of America, using the contingent valuation method, estimated an average of DAP of $ 5.49 dollars monthly, over the rate that were already paying, and those with access to private wells up to $ 7.38 dollars. However, Polyzou et al (2011) found that, for different reasons, not always the users of drinking water service are willing to pay for an upgrade as they found that only 40% of respondents were willing to contribute some amount to improve the quality of drinking water.…”
Section: Materiales Y Métodosmentioning
confidence: 99%